Variable assessment of wing colouration in aerial contests of the red-winged damselfly Mnesarete pudica (Zygoptera, Calopterygidae) - Guillermo-Ferreira, Rhainer; Gorb, Stanislav N.; Appel, Esther; Kovalev, Alexander; Bispo, Pitágoras da Conceição [UNESP] (Springer, 2015)
Wing pigmentation is a trait that predicts the outcome of male contests in some damselflies. Thus, it is reasonable to suppose that males would have the ability to assess wing pigmentation and adjust investment in a fight according to the costs that the rival may potentially impose. Males of the damselfly Mnesarete pudica exhibit red-coloured wings and complex courtship behaviour and engage in striking male-male fights. In this study, we investigated male assessment behaviour during aerial contests. Theory suggests that the relationship between male resource-holding potential (RHP) and contest duration describes the kind of assessment adopted by males: self-assessment, opponent-only assessment or mutual assessment. A recent theory also suggests that weak and strong males exhibit variations in the assessment strategies adopted. We estimated male RHP through male body size and wing colouration (i.e. pigmentation, wing reflectance spectra and transmission spectra) and studied the relationship between male RHP and contest duration from video-documented behavioural observations of naturally occurring individual contests in the field. The results showed that males with more opaque wings and larger red spots were more likely to win contests. The relationships between RHP and contest durations partly supported the self-assessment and the mutual assessment models. We then experimentally augmented the pigmented area of the wings, in order to evaluate whether strong and weak males assess rivals'RHP through wing pigmentation. Our experimental manipulation, however, clearly demonstrated that strong males assess rivals'wing pigmentation. We finally suggest that there is a variation in the assessment strategy adopted by males.
Keywords: Dragonfly; Game theory; Territoriality; Competition; Ornament